Update Breast Cancer 2023, Part 2, Advanced-stage breast cancer = Update Mammakarzinom 2023, Teil 2, Brustkrebs in fortgeschrittenen Krankheitsstadien - Lux, Michael Patrick; Thomssen, Christoph; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2023)
Breast cancer - metastatic - endocrine therapy - antibody drug conjugate - chemotherapy